Reply to Comments on "the Cenozoic Fold‐and‐Thrust Belt of Eastern Sardinia: Evidences from the Integration of Field Data With Numerically Balanced Geological Cross Section" by Arragoni et al. (2016). Issue 10 (17th October 2017) - Salvini, F.; Arragoni, S.; Cianfarra, P.; Maggi, M.
Abstract: The comment by Berra et al. (2017) on the evidence of Alpine tectonics in Eastern Sardinia proposed by Arragoni et al. (2016) is based on the sedimentological interpretations of few local outcrops in a marginal portion of the study area. The Cenozoic Alpine fold‐and‐thrust setting, which characterizes this region, presents flat‐over‐flat shear planes acting along originally stratigraphic contacts, where stratigraphic continuity is obviously maintained. The ramp sectors present steeply dipping bedding attitudes, and there is no need to invoke and to force prograding clinoforms with unrealistic angles to justify them. The balanced geological cross section proposed by Arragoni et al. (2016) is fully supported by robust newly collected structural data and is compatible with the overall tectonic setting, while the interpretation proposed by Berra et al. (2017) lacks a detailed structural investigation. We believe that the partial application of the techniques available to modern geology may lead to incorrect interpretations, thus representing an obstacle for the progress of knowledge in the Earth sciences. Key Points: A Cenozoic Alpine fold‐and‐thrust belt is present in Eastern Sardinia with WSW vergence The Paleozoic basement and the Mesozoic sedimentary cover are involved in the thrust belt This belt formed in Cenozoic time before the Miocene opening of the Tyrrhenian Sea